2017
DOI: 10.4314/ejhs.v27i6.2
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of <i>Helicobacter pylori</i> among Dyspeptic patients attending at University of Gondar Hospital, Gondar, Northwest Ethiopia

Abstract: Background Helicobacter pylori (H.pylori) infection is predominantly acquired in childhood from family members. The infection can cause dypepepsia, chronic and acute gastritis and gastric cancer. Dyspepsia is the most common illness in the Ethiopian population visiting outpatient department of health facilities, and it has also been associated with H.pylori infection. The aim of this study was to assess the magnitude of H.pylori and its associated factors among dyspeptic patients who visited Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
2
13
2
1
Order By: Relevance
“…The prevalence of H. pylori in dyspeptic patients in Northwest Ethiopia was 43% in males and 32% in females, 16 and higher in Ghana: 71.1%. 17 In the latter study population, vacAs1 was present in 69.2%, vacAm1 in 44.7%, vacAm2 in 22.0%, and cagA in 74.8%; but vacAs1/cagA+ was found in 72.6% of the H. pylori positive individuals.…”
Section: Africamentioning
confidence: 89%
“…The prevalence of H. pylori in dyspeptic patients in Northwest Ethiopia was 43% in males and 32% in females, 16 and higher in Ghana: 71.1%. 17 In the latter study population, vacAs1 was present in 69.2%, vacAm1 in 44.7%, vacAm2 in 22.0%, and cagA in 74.8%; but vacAs1/cagA+ was found in 72.6% of the H. pylori positive individuals.…”
Section: Africamentioning
confidence: 89%
“…1 Whereas a large amount of population was affected in different parts of Ethiopia, the percentage varies from 36.8% to 83.3% across the country. [3][4][5][6][7][8] H. pylori infection is acquired in early childhood through fecal-oral or oral-oral transmission and becomes a chronic infection if left untreated. 9 It possesses different mechanisms to colonize the host and can result in several gastrointestinal diseases, including gastritis, peptic ulcer, duodenal ulcer, and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Negash et al found that the rapid SAT had a slightly better performance than the serological test available at that time in Ethiopia. Besides, in one cross‐sectional study for H. pylori infection diagnosis, the exact same SAT (Guangzhou Wondfo Biotech, China) was used . One study using an SAT found it to be a cost‐effective and rapid method for initial screening of H. pylori infection …”
Section: Noninvasive Testsmentioning
confidence: 99%
“…Besides, in one cross-sectional study for H. pylori infection diagnosis, the exact same SAT (Guangzhou Wondfo Biotech, China) was used. 30 One study using an SAT found it to be a costeffective and rapid method for initial screening of H. pylori infection. 31 Moon et al analyzed the relationship between the serum pepsinogen (PG) level and SAT in 318 H. pylori-seropositive patients.…”
Section: Stool Antigen Test (Sat)mentioning
confidence: 99%